Add and subtract polynomials 10(u+v)+8(u-1)-3(u+6) @michele_laino

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

What do I have to do first?
Simplifying -10(u + v) + 8(u + -1) + -3(u + 6) = 0 (u * -10 + v * -10) + 8(u + -1) + -3(u + 6) = 0 (-10u + -10v) + 8(u + -1) + -3(u + 6) = 0 Reorder the terms: -10u + -10v + 8(-1 + u) + -3(u + 6) = 0 -10u + -10v + (-1 * 8 + u * 8) + -3(u + 6) = 0 -10u + -10v + (-8 + 8u) + -3(u + 6) = 0 Reorder the terms: -10u + -10v + -8 + 8u + -3(6 + u) = 0 -10u + -10v + -8 + 8u + (6 * -3 + u * -3) = 0 -10u + -10v + -8 + 8u + (-18 + -3u) = 0 Reorder the terms: -8 + -18 + -10u + 8u + -3u + -10v = 0 Combine like terms: -8 + -18 = -26 -26 + -10u + 8u + -3u + -10v = 0 Combine like terms: -10u + 8u = -2u -26 + -2u + -3u + -10v = 0 Combine like terms: -2u + -3u = -5u -26 + -5u + -10v = 0 Solving -26 + -5u + -10v = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '26' to each side of the equation. -26 + -5u + 26 + -10v = 0 + 26 Reorder the terms: -26 + 26 + -5u + -10v = 0 + 26 Combine like terms: -26 + 26 = 0 0 + -5u + -10v = 0 + 26 -5u + -10v = 0 + 26 Combine like terms: 0 + 26 = 26 -5u + -10v = 26 Add '10v' to each side of the equation. -5u + -10v + 10v = 26 + 10v Combine like terms: -10v + 10v = 0 -5u + 0 = 26 + 10v -5u = 26 + 10v Divide each side by '-5'. u = -5.2 + -2v Simplifying u = -5.2 + -2v
So, for the first part I have to distributive property. Correct?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

yes
here you have to apply the distributive propery of multiplication over addition, so we can write: \[\Large \begin{gathered} 10\left( {u + v} \right) + 8\left( {u - 1} \right) - 3\left( {u + 6} \right) = \hfill \\ \hfill \\ = 10u + 10v + 8u - 8 - 3u - 18 = ... \hfill \\ \end{gathered} \] please simplify
Hint: next step is: \[\Large \begin{gathered} 10\left( {u + v} \right) + 8\left( {u - 1} \right) - 3\left( {u + 6} \right) = \hfill \\ \hfill \\ = 10u + 10v + 8u - 8 - 3u - 18 = \hfill \\ \hfill \\ = \left( {10 + 8 - 3} \right)u + 10v - 8 - 18 = ... \hfill \\ \end{gathered} \]
I am so confused
why?
you have to combine like terms
|dw:1434402027289:dw| Is that correct?
15 u is right 10 v is right whereas we have -18-8=-26, and not 18-8
But 8-18 equals - 10
nvm it is +10 So the answer is 15u + 10 v +10
yes! nevertheless, we have: 8(u-1)-3(u+3)=8u-8-3u-18, so the answer contains -8-18=-26
oops..-3(u+6)
so the answer is: 15u + 10 v - 26?
that's right!
oh now I get it thanks. ☺
:)
so you know how there is a - sign right where: -3(u+6) don't you have to change the - sign to a + sign and the you have +3(-u-6) -3u - 18 which when I write the equation I have: 10 u + 10 v + 8 u - 8 - 3 u +18 ___________________ So 10 u + 8 u equals 18u which then you have to subtract by 3 which is 15u. Then I keep 10 v the same. -8 + 10 = 10 So the answer should be: 15 u + 10 v + 10 10 u + 10 v +8 u - 8 -3 u +18 ____________________ 15 u + 10 v + 10

Not the answer you are looking for?

Search for more explanations.

Ask your own question